Mechanism of Rhinovirus Immunity and Asthma - Yang, Zuqin; Mitländer, Hannah; Vuorinen, Tytti; Finotto, Susetta (Frontiers in Immunology, 2021)
The majority of asthma exacerbations in children are caused by Rhinovirus (RV), a positive sense single stranded RNA virus of the Picornavirus family. The host has developed virus defense mechanisms that are mediated by the upregulation of interferon-activated signaling. However, the virus evades the immune system by inducing immunosuppressive cytokines and surface molecules like programmed cell death protein 1 (PD-1) and its ligand (PD-L1) on immunocompetent cells. Initially, RV infects epithelial cells, which constitute a physiologic mucosal barrier. Upon virus entrance, the host cell immediately recognizes viral components like dsRNA, ssRNA, viral glycoproteins or CpG-DNA by host pattern recognition receptors (PRRs). Especially through toll like receptors (TLR) 3, 7 and 8 within the endosome and through MDA-5 and RIG-I in the cytosol, leading to the production of interferon (IFN) type I and other antiviral agents. Every cell type expresses IFNAR1/IFNAR2 receptors thus allowing a generalized antiviral activity of IFN type I resulting in the inhibition of viral replication in infected cells and preventing viral spread to non-infected cells. Amongst the immune evasion mechanisms of the virus, there is the downregulation of IFN type I and its receptor and the induction of the immunosuppressive cytokine TGF-β that is known to induce rhinovirus replication. We recently analyzed TGF-β and its signal transduction after RV challenge of peripheral blood mononuclear cell (PBMCs) from healthy and asthmatic children. Here we found that, in vitro infection of PBMCs resulted in increased cellular uptake of TGF-β associated with induction of immunosuppression signature markers like LAP3, IDO and PD-L1. In summary, this suggests that RV infection uses active TGF-β present in the environment, like in chronic asthma, to replicate and to inhibit effective antiviral immune responses. Moreover, we recently described increased level of PD-L1 mRNA in total blood cells isolated from preschool children with virus-induced asthma, with lower percentage of forced expiratory volume in 1 second (FEV1) and with high serum levels of the C-reactive-protein. This article reviews the recent advances of the literatures on the regulated expression of type I interferons in association with RV infection in asthmatics and the immunosuppression induced by the virus.